Pneumothorax in critically ill patients with COVID-19 infection: Incidence, clinical characteristics and outcomes in a case control multicenter study. (August 2021) - Chopra, Amit; Al-Tarbsheh, Ali Hani; Shah, Nidhi J.; Yaqoob, Hamid; Hu, Kurt; Feustel, Paul J.; Ortiz-Pacheco, Ronaldo; Patel, Kinner M.; Oweis, Jozef; Kozlova, Natalya; Zouridis, Spyridon; Ahmad, Sahar; et al.
Abstract: Background: The clinical features and outcomes of mechanically ventilated patients with COVID-19 infection who develop a pneumothorax has not been rigorously described or compared to those who do not develop a pneumothorax. Purpose: To determine the incidence, clinical characteristics, and outcomes of critically ill patients with COVID-19 infection who developed pneumothorax. In addition, we compared the clinical characteristics and outcomes of mechanically ventilated patients who developed a pneumothorax with those who did not develop a pneumothorax. Methods: This study was a multicenter retrospective analysis of all adult critically ill patients with COVID-19 infection who were admitted to intensive care units in 4 tertiary care centers in the United States. Results: A total of 842 critically ill patients with COVID-19 infection were analyzed, out of which 594 (71%) were mechanically ventilated. The overall incidence of pneumothorax was 85/842 (10%), and 80/594 (13%) in those who were mechanically ventilated. As compared to mechanically ventilated patients in the non-pneumothorax group, mechanically ventilated patients in the pneumothorax group had worse respiratory parameters at the time of intubation (mean PaO2 :FiO2 ratio 105 vs 150, P<0.001 and static respiratory system compliance: 30ml/cmH2 O vs 39ml/cmH2 O, P = 0.01) and significantly higher in-hospital mortality (63% vs 49%, P = 0.04). Conclusion: The overall incidence of pneumothorax in mechanically ventilated patients with COVID-19 infection was 13%. Mechanically ventilated patients with COVID-19 infection who developed pneumothorax had worse gas exchange and respiratory mechanics at the time of intubation and had a higher mortality compared to those who did not develop pneumothorax. Highlights: The incidence of pneumothorax was 10% in critically ill and 13% in mechanically ventilated patients with COVID-19 infection. Patients who developed a pneumothorax had greater severity of lung disease as compared to those without pneumothorax. Odds of in-hospital death were increased nearly two-fold in those who had a pneumothorax as compared to those without pneumothorax.